Posición sistemática de Akodon (Abrothrix) kermacki y A. (Ab.) magnus (Rodentia, Cricetidae) del plio-pleistoceno del sudeste de Buenos Aires, Argentina - Teta, Pablo Vicente (2014)
The taxonomic status of the fossil sigmodontine rodents Akodon (Abrothrix) kermacki Reig 1978 and A. (Ab.) magnus Reig 1987 (PlioPleistocene, Buenos Aires Province) was revised. Based on molar morphology and other cranial traits of the type specimens, and considering the current defi nition of the Abrotrichini, we suggest that both taxa are not member of this tribe. These fossil forms are preliminarily referred to Akodontini, pending of further studies for a fi nal taxonomic identity. In addition, some biogeographical considerations about the Abrotrichini evolution based on this new taxonomic scenario are presented.